[Afisz. Incipit] Program aktualności krajowych i zagranicznych nr 1 ... (Gdynia : [wydawca nieznany], 1948)
Afisz z repertuarem kina Warszawa na 26.04-2.05.1948 r.
Keywords: Kina -- Polska -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- druki ulotne; Afisze -- 1945-1990.